Attributors of workplace bullying : cleaning workforces' perspective / Aslinda Ramely and Yarina Ahmad - Ramely, Aslinda; Ahmad, Yarina (Universiti Teknologi MARA, Shah Alam, 2017)
Known as a universal phenomenon, workforce bullying has become one of the inequalities that obstruct the creation of internal customer and market orientations that hinder the continuous development of the superior performance of the organisation. Aside from that, these unwelcomed incidences have also been proven to bring about numerous adverse consequences to the society especially to the victims and their family. Therefore, this paper believes that the issue of workplace bullying is analytically and critically in need of comprehension; so that the supportive environment in workplaces can be created and yet, assist in bringing mutual benefit to the organisation, employees, and society. For this purpose, this paper aims to discuss the attributors of workplace bullying by seeking answers from the perspective of the cleaning workforce in organisations since they have been categorised as a bottom-ranked position and their voices are unheard and are always ignored. Hence, this study utilises the quantitative approach by distributing surveys involving 248 cleaners in Selangor. The findings of this study revealed that interpersonal conflicts and poor physical work environments have significantly influenced workforce bullying (p<0.01, p<0.05) whereas poor leadership was found to have no significant influence towards workforce bullying. Notably, the main factor that influences workforce bullying was interpersonal conflict (p<0.01, β = 0.368). While it is proven that workforce bullying is occur, this paper believe further corrective actions is need to be implemented so that the situation is not getting worse. Therefore, this study also discusses on several recommendations that are useful to be implemented by all organisations in overcoming workplace bullying. These recommendations are inclusive of primary, secondary, and tertiary interventions.